2020
DOI: 10.1126/sciadv.aaz8011
|View full text |Cite
|
Sign up to set email alerts
|

Particle-based artificial three-dimensional stem cell spheroids for revascularization of ischemic diseases

Abstract: Development of new approaches to biomimetically reconstruct vasculature networks remains challenging in regenerative medicine. We introduce a particle-based artificial stem cell spheroid (ASSP) technology that recapitulates paracrine functions of three-dimensional (3D) SSPs for vasculature regeneration. Specifically, we used a facile method to induce the aggregation of stem cells into 3D spheroids, which benefited from hypoxia microenvironment–driven and enhanced secretion of proangiogenic bioactive factors. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 48 publications
(57 reference statements)
0
53
0
Order By: Relevance
“…[ 23 ] Our previous studies demonstrated FTn as a promising nanocarrier capable of actively binding with hypoxic cells to provide efficient tissue penetration, predominantly through interactions with its receptor (TfR‐1 in humans; TIM‐2 in mice). [ 24 ] In addition to active targeting of FTn, we previously demonstrated that increased vessel permeability contributed to the improved nanoparticle accumulation in ischemic tissue, [ 25 ] revealing the targeting ability of FTn to be dependent on both active and passive mechanisms.…”
Section: Figurementioning
confidence: 99%
“…[ 23 ] Our previous studies demonstrated FTn as a promising nanocarrier capable of actively binding with hypoxic cells to provide efficient tissue penetration, predominantly through interactions with its receptor (TfR‐1 in humans; TIM‐2 in mice). [ 24 ] In addition to active targeting of FTn, we previously demonstrated that increased vessel permeability contributed to the improved nanoparticle accumulation in ischemic tissue, [ 25 ] revealing the targeting ability of FTn to be dependent on both active and passive mechanisms.…”
Section: Figurementioning
confidence: 99%
“…For example, MSC spheroids constructed by inducing cell–cell aggregation via supplement of a cell adhesion cue improved MSC survival and retention, and their therapeutic efficacy for treating ischemic diseases, as demonstrated by a 20‐ to 70‐fold upregulation in angiogenic factors VEGF, PDGF, IGF, as well as 1250‐ to 1400‐fold increase in epidermal growth factor (EGF) and angiopoietin‐1(Ang‐1) expression ( Figure ). [ 112 ] Through an alternative approach a hybrid MSC/PEGylated‐DNA nanocomposite spheroid was generated for the treatment of glioblastoma. The MSCs were engineered to express TNF‐related apoptosis‐inducing ligand (TRAIL) while the PEGylated DNA facilitated colloidal stability upon calcium phosphate‐mediated nanoprecipitation and allowed the loading of mitoxantrone, a drug that could sensitize the response of TRAIL in glioblastoma.…”
Section: Delivery Strategies To Improve Therapeutic Effect Of the Mscmentioning
confidence: 99%
“…Despite encouraging results, the clinical efficacy is limited by the short half‐life in the pathological environment. [ 3 ] The delivery of pro‐angiogenic growth factors, nucleic acids, and stem or vascular cells [ 6 ] and cell‐free therapies have been the focus of the emerging therapeutic strategies. [ 6,7 ] Many of these non‐traditional strategies have shown their promising effects in pre‐clinical and, in some cases, clinical trials promoting the formation of new blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] The delivery of pro‐angiogenic growth factors, nucleic acids, and stem or vascular cells [ 6 ] and cell‐free therapies have been the focus of the emerging therapeutic strategies. [ 6,7 ] Many of these non‐traditional strategies have shown their promising effects in pre‐clinical and, in some cases, clinical trials promoting the formation of new blood vessels. [ 8 ] However, despite the beneficial outcomes, each of these approaches continue to present several translational challenges and limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation